"Kochom swoje wioske, bom sie w ni rodzieła". Wilkowsko-świętokrzysko-kielecka poezja Kaśki spod Łysicy w świetle refleksji językoznawczo-kulturologicznych = "Kochom swoje wioske, bom sie w ni rodzieła" [I lov my villag cause I was born in't]. Wilków-Świętokrzyskie-Kieleckie poetry by Kaśka spod Łysicy in the lights of linguistic and culturological reflections - Węgorowska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The text is devoted to the oral poetry by Kaśka spod Łysicy - Katarzyna Zaborowska from Wilków, Świętokrzyskie Region. Linguistic-culturological reflection concerns the onyms (toponyms, microtoponyms, oronyms, antroponyms), appellatives and dialect and subdialect distinctive features. An insightful interpretation of these complementary elements permitted to determine the specific features of the idiolect of the forgotten poet.
Keywords: poezja; gwara; dialekt; onimy; apelatywy; poetry; subdialect; dialect; onyms; appelatives